The role of CD68+ and CD163+ macrophages in immunopathogenesis of oral lichen planus and oral lichenoid lesions - Ferrisse, Túlio Morandin [UNESP]; de Oliveira, Analú Barros [UNESP]; Palaçon, Mariana Paravani [UNESP]; Silva, Evânio Vilela [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; de Almeida, Luciana Yamamoto; Léon, Jorge Esquiche; Bufalino, Andreia [UNESP] (Elsevier, 2021)
Macrophages are phagocytic cells with essential participation in immunological events of the oral cavity. However, the role of these cells in oral lichen planus (OLP) and oral lichenoid lesions (OLL) remains unclear. The present study aimed to evaluate the density of macrophages in OLP and OLL, and to compare it with that of oral inflammatory fibrous hyperplasia (OIFH) (control group). 14 cases of OLP, 14 cases of OLL and 14 cases of OIFH were selected for immunohistochemical analysis of CD68+ (M1) and CD163+ (M2) macrophage expression. CD68+ and CD163+ macrophages densities were measured in the intraepithelial and subepithelial areas. The statistical tests used were multivariate analysis of variance, as well as a correlation and linear regression. OLP has more CD68+ macrophages when comparing with OLL (p = 0.001) and OIFH (p = 0.045). There is a very strong relationship between the macrophages types (p < 0.0001) in OLP and OLL. The linear regression showed that to OLL development (p < 0.0001/R2′ = 0.9584), the presence of different types of macrophages are more essential than to OLP (p < 0.0001/R2′ = 0.8983). However, in the OLP these dependencies are also largely. CD68+ macrophages may be associated with immunopathogenesis of OLP, indicating a pro-inflammatory activity and regulatory role in the type of T-cell response. Besides, CD68+ macrophages can cooperate in the diagnosis of OLP. These results are essential to future studies that seek a therapeutic target for OLP and OLL.
Keywords: Immunohistochemistry; Immunopathogenesis; Macrophages; Multivariate analysis; Oral lichen planus; Oral lichenoid lesion; Oral potentially malignant disorders